The Role of Servant Leadership in Imrpoving Entrepreneurial Mindset, Climate, Knowledge Management, Organization Development and Its Impact on Higher Education Performance - Muhammad Ramaditya; Friska Intan Sundari (School of Business, IPB University (SB-IPB), 2023)
For higher education to continue in the education sector, they must perform better. The purpose of this study is to investigate the effects of organizational development, knowledge management, entrepreneurial atmosphere, servant leadership, and entrepreneurial mentality on performance in private higher education in the LLDikti III region. This study employs a quantitative approach, namely a survey method that gathers data through the use of a questionnaire. Lecturers from private universities in the LLDikti III region made up the study's population. The sample in this study was 376 respondents. The analysis tool used is SmartPLS 3 with Structural Equation Modeling based on Partial Least Square. The results of this study state that higher education performance can be improved by having servant leadership, entrepreneurial climate, entrepreneurial mindset, and organization development. Private higher education needs to be more concerned to become entrepreneurial activities in their organization if they want to stay relevant in the industry. Keywords: entrepreneurial mindset, entrepreneurial climate, higher education performance, servant leadership, organizational development